2013
DOI: 10.20473/ijtid.v4i4.233
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS ON WHOLE BLOOD, SGOT, SGPT, AND TNF-a EXAMINATION IN PATIENTS WITH NON-DENGUE AND POSITIVE DENGUE FEVER (DF/DHF)

Abstract: Background: In Indonesia has four serotypes, the DEN-1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…As the standard deviation is more than centrality measure (mean/median), the statistical relevance of central values is lost. In other larger studies, SGOT was conclusively found raised in dengue [12,13].…”
Section: Sgotmentioning
confidence: 66%
See 2 more Smart Citations
“…As the standard deviation is more than centrality measure (mean/median), the statistical relevance of central values is lost. In other larger studies, SGOT was conclusively found raised in dengue [12,13].…”
Section: Sgotmentioning
confidence: 66%
“…As the standard deviation is more than centrality measure (mean/median), the statistical relevance of central values is lost. In a larger study, too SGPT was found normal in dengue fever (rather it was raised in non-dengue fever) [12], while, in another study, this normalcy was equivocal [13].…”
Section: Sgptmentioning
confidence: 77%
See 1 more Smart Citation
“…SGPT levels after therapy in the standard group + guava leaf extract capsules were lower than before therapy as well as the standard therapy or control group. Case report research by Anggraini & Nasronudin (2013) on non-dengue SGOT and SGPT levels increased 1-3x normal value and in dengue positive fever SGOT levels increased 1-3 times the normal value, but at SGPT levels were still within normal limits with a value of p = 0.022. SGPT and bilirubin levels rarely increase in dengue fever patients compared to SGOT level.…”
Section: Results Researchmentioning
confidence: 93%
“…Nilai kadar SGPT mengalami peningkatan pada penderita demam berdarah dikarenakan terdapat kerusakan pada jaringan hati yang diakibatkan oleh virus dengue tetapi kenaikan kadar SGPT masih di batas normal karena enzim SGPT ditemukan paling banyak di organ hati, pernyataan ini sejalan dengan penelitian sebelumnya yang dilakukan oleh Santosa et al (2010), dimana pada peningkatan kadar enzim transaminase selama difase demam dapat menjadi penanda untuk pembeda antara adanya infeksi virus dengue dengan infeksi virus yang lainnya hal ini juga sejalan dengan penelitian yang dilakukan oleh Saudo et al (2016), yang menyatakan bahwa terjadinya peningkatan kadar enzim transaminase dapat menjadi penanda potensial untuk membedakan infeksi virus dengue dari virus lain selama fase demam, sehingga deteksi peningkatan enzim transaminase sejak dini pada pasien dengue sangatlah penting untuk mencegah terjadinya komplikasi infeksi dengue yang biasa disebut hepatik ensefalopati. Tingkat keparahan disfungsi hati pada pasien penderita demam berdarah dengue dapat dikaitkan dengan tingkat keparahan penyakit dengue itu sendiri hal ini juga sesuai dengan penelitian yang dilakukan oleh Anggraini and Nasronudin (2013) tentang analysis on whole blood, SGOT, SGPT, and TNF-A examination in patient.…”
Section: Hasil Dan Pembahasanunclassified